Herpetic anterior uveitis following COVID-19 vaccines: a case series - Ott, Muriel; Nagamany, Thanoosha; Zandi, Souska; Pichi, Francesco; Agarwal, Aniruddha; Carreño, Ester; Gupta, Vishali; Grewal, Dilraj S.; Cunningham, Emmett T.; Munk, Marion R. (Frontiers in Medicine, 2023)
Purpose: To report a case series of herpetic uveitis following COVID-19 vaccinations.2 Methods: Demographic, clinical and treatment-related data of herpetic anterior uveitis cases was collected at five tertiary eye hospitals between January 2021 and June 2022. A retrospective database review at one of the centers comparing the number of cases of herpetic eye disease before and after the introduction of COVID-19 vaccination was performed as well.Results: Twenty-four patients (9 female, 15 male) with a mean age of 54 years (range 28-83 years) were diagnosed with herpetic uveitis, reporting an onset of symptoms 3 to 42 days after the first, second or third dose of COVID-19 vaccination. Median time between vaccination and onset of herpetic eye disease was 10 days (mean 12.7±10.15 days) days. The administered vaccines were BNT162b2, mRNA-1273, BBIBP-CorV and Ad26.COV2.S. The cases included 11 HSV, 10 VZV and 1 CMV anterior uveitis, 2 were not further specified. There was an equal number of first episodes (n=12, 50%) and recurrent episodes (n=12, 50%). Response to established regimens was generally good. The retrospective database review revealed the exact same incidence of herpetic uveitis during the pandemic and ongoing vaccination compared to prior SARS-COV2.Conclusions: This report includes 24 cases of herpetic anterior uveitis in a temporal relationship to various COVID-19 vaccines. This study supports the potential risk of herpetic eye disease following COVID-19 vaccines, but proof of a direct, causal relationship is missing.